Interpreters’ Perception of Linguistic and Non-Linguistic Factors Affecting Quality: A Survey through the World Wide Web - Chiaro, Delia; Nocella, Giuseppe (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2004)
AbstractThis paper will present and discuss the results of an empirical study on perception of quality in interpretation carried out on a sample of 286 interpreters across five continents.Since the 1980’s the field of Interpreting Studies has been witnessing an ever growing interest in the issue of quality in interpretation both in academia and in professional circles, but research undertaken so far is surprisingly lacking in methodological rigour. This survey is an attempt to revise previous studies on interpreters’ perception of quality through the implementation of new Information Technology which allowed us to administer a traditional research tool such as a questionnaire, in a highly innovative way; i.e., through the World Wide Web. Using multidimensional scaling, a perceptual map based upon the results of the manner in which interpreters ranked a list of linguistic and non-linguistic criteria according to their perception of importance in the interpretative process, was devised.